2001
DOI: 10.1093/cercor/11.9.878
|View full text |Cite
|
Sign up to set email alerts
|

An Endogenous Adrenoceptor Ligand Potentiates Excitatory Synaptic Transmission in Cultured Hippocampal Neurons

Abstract: Noradrenergic inputs modulate hippocampal function via distinct receptors. In hippocampal neuronal cultures, mRNA expression of adrenoceptor subtypes is maintained from 1 day in vitro (DIV) to 22 DIV. Noradrenaline dose-dependently stimulates phosphoinositide (PI) breakdown in both immature and mature cultures through the activation of alpha1 receptors. At 22 DIV, basal PI breakdown depends on excitatory synaptic activity since it is decreased by tetrodotoxin or glutamate receptor antagonists. At 22 DIV, a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
2
14
1
Order By: Relevance
“…2). The data are in line with the finding that α 1 ‐antagonism inhibits spontaneous excitatory synaptic activity in cultured hippocampal neurons (Aubert et al. 2001) but contrasts to previous in vitro investigations showing α 1 ‐adrenoreceptors to pre‐synaptically inhibit Glu release in the CA3 hippocampal area (Scanziani et al.…”
Section: Discussionsupporting
confidence: 84%
“…2). The data are in line with the finding that α 1 ‐antagonism inhibits spontaneous excitatory synaptic activity in cultured hippocampal neurons (Aubert et al. 2001) but contrasts to previous in vitro investigations showing α 1 ‐adrenoreceptors to pre‐synaptically inhibit Glu release in the CA3 hippocampal area (Scanziani et al.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, experiments made on neurons of layer V of the medial prefrontal cortex and in mature cultured hippocampal neurons showed that activation of α1-ARs increase the frequency but not the amplitude of sEPSC. No differences were found on mEPSC (Marek and Aghajanian, 1999, Aubert et al, 2001). In accordance with the latter data, our results showed that enhancement of EPSCs by α1-AR activation is dependent on presynaptic action potentials given that the increased frequency was not observed in the presence of TTX, an established inhibitor of voltage-gated sodium channels (Narahashi et al, 1967).…”
Section: Discussionmentioning
confidence: 74%
“…The effects of α1-AR stimulation on spontaneous synaptic transmission have been previously assessed with contradictory results in cultured rat hippocampal neurons, and in brain slices of hypothalamus and cerebral cortex (Marek and Aghajanian, 1999, Aubert et al, 2001, Gordon and Bains, 2003, Dong et al, 2005, Gordon and Bains, 2005). Investigations on different nuclei of the hypothalamus and prelimbic cortex preparations have demonstrated that α1-AR activation increase mEPSC frequency.…”
Section: Discussionmentioning
confidence: 99%
“…L-Phe is the direct precursor of tyrosine, which in turn is metabolized to dopamine and norepinephrine. Although in the adult hippocampus norepinephrine is released mainly by fibers originating from the locus coeruleus (Loy et al, 1980), Aubert et al (2001) showed that cultured hippocampal neurons possess both tyrosine hydroxylase (TH) and dopamine-␤-hydroxylase mRNAs, and some hippocampal neurons show TH immunoreactivity. In addition, the presence of TH immunoreactivity has been reported in hippocampal cells under specific conditions, including colchicine-treated rats during development (Siddiqui et al, 1995) and following complex partial seizures in humans (Zhu et al, 1990).…”
Section: Mechanism(s) Of the Depressant Effect Of L-phe On Glur Functionmentioning
confidence: 99%